Driving Business Success: How Motivation, Compensation, and Work Environment Affect Marketing Performance in Banking Sector - Yuniari, Ni Nyoman Sri; Telagawathi, Ni Luh Sayang; Heryanda, Komang Krisna (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the simultaneous influence of motivation, compensation, and work environment on the performance of marketing employees at Bank BNI Singaraja Branch. Using a quantitative research design and a survey method, data were collected through a structured questionnaire distributed to all 35 marketing employees. The collected data were rigorously tested for validity and reliability before being analyzed using multiple regression analysis with SPSS version 20. The results indicate that the independent variables—motivation, compensation, and work environment—collectively and significantly explain variations in employee performance. Specifically, the findings suggest that improvements in these three aspects are associated with increased productivity, efficiency, and overall performance in the marketing department. These results highlight the importance of an integrated human resource management strategy, emphasizing consistent motivation programs, fair and competitive compensation, and a supportive work environment. The strategic implications of this study suggest that optimizing these factors can enhance organizational goal achievement and provide a sustainable competitive advantage in the banking sector.